WEBSITE DESIGN ACADEMY FANTASI INDOSIAR 2 USING MACROMEDIA DREAMWEAVER MX 2004 - Eka Yunita Ratma (Jurnal Sistem Informasi, 2006)
Today's technology is growing rapidly where humans much needed information fast-paced, especially with internet facility which began ogled as a media campaign that quite interesting. To the authors wanted to provide news and information about the Academy Indosiar Fantasy 2 (AFI 2) to users who want to know more about the Akademia AFI 2. The site is expected to provide facilities for people in general and the AFI Fans 2 (2 Mania AFI).